El Excentrico, 1969-11-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
November 20, 1969 [20 de noviembre de 1969]. No volume or cover number. Cover has a photo of a salesman, Wilford Irizarry, who had started working for the American Pontiac company at the time of theis issues's release.